1999
DOI: 10.1016/s0925-4439(99)00021-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute oxidative stress modulates secretion and repetitive Ca2+ spiking in rat exocrine pancreas

Abstract: The effects of the oxidant tert-butylhydroperoxide (t-buOOH) on carbachol-stimulated pancreatic secretion in the vascularly perfused rat pancreas have been studied in parallel with [Ca2+]i signalling and amylase output in perifused rat pancreatic acinar cells. Perfusion of the pancreas with t-buOOH (0.1-1 mM) caused a rapid and irreversible inhibition of carbachol-stimulated (3x10-7 M) amylase and fluid secretion. Pre-perfusion of the pancreas with vitamin C and dithiothreitol or a cocktail of GSH and GSH-prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…To determine whether any Ca 2ϩ signaling response or change in cell viability was mediated by free radicals, a further group of cell-agarose constructs was treated with the antioxidant, ascorbate (16,26,29,34). Constructs were incubated in EBSS supplemented with 1 mM ascorbate (Sigma) for 10 min before and throughout the 1-h confocal imaging protocol as indicated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether any Ca 2ϩ signaling response or change in cell viability was mediated by free radicals, a further group of cell-agarose constructs was treated with the antioxidant, ascorbate (16,26,29,34). Constructs were incubated in EBSS supplemented with 1 mM ascorbate (Sigma) for 10 min before and throughout the 1-h confocal imaging protocol as indicated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to cytosolic calcium impairment, oxidative stress has also been involved in abnormal enzyme acti vation during the early phase of AP [30] . Excessive oxygen radical formation from activated leukocytes [31] leads to oxidative stress and pathological processes. In experimental AP, superoxide radical accumulation could lead to cell cytoskeleton dysfunction leading to intracellular transport impairment and premature activation of digestive enzymes [30] .…”
Section: Initial Pathophysiological Events In Apmentioning
confidence: 99%
“…In relation to this, treatment with vitamin C restored impaired Ca 2+ signaling and maintained amylase output impaired by oxidative stress (Sweiry et al, 1999). In a later study, we showed that the oxidant hydrogen peroxide (H 2 O 2 ) inhibited amylase secretion in response to cholecystokinin.…”
Section: Introductionmentioning
confidence: 78%